The impact of different types of orthodontic appliances and its location in producing CT scan artefacts - Mohammed, Mahmud; Norma Ab. Rahman,; Ahmad Hadif Zaidin Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Fixed orthodontic appliances can produce metal artefacts in CT images which may degrade the diagnostic image quality. The study aimed to evaluate the artefacts based on the types and location of the metallic and non-metallic orthodontic brackets. This is an in-vitro cross-sectional study. Four different types of orthodontic brackets (stainless steel, titanium, monocrystalline, and polycrystalline ceramic bracket) were bonded consecutively in four different locations of the cadaveric skull. All scans were performed by a single operator using the same CT machine followed by a standard scanning protocol. Artefact intensity for all data sets was quantified by calculating the standard deviation (SD) of the grey values within the dataset by following a standard method. The One-way ANOVA Bonferroni test was used for the data analysis. The mean artefact score of the stainless steel bracket was significantly (p < 0.001) high in comparison with other types of the orthodontic brackets. Besides, the mean artefact score was significantly (p=0.002) low when orthodontic brackets were placed unilaterally. Stainless steel brackets produced a significant amount of noise in CT images which can degrade the diagnostic image quality. Thus, the polycrystalline ceramic bracket can be a better alternative of stainless steel brackets for patient need frequent CT scan.